Principles and application of tunnel gravity full-space positioning and detection method for deep high-density vertical orebodies - Wang, Jiyu; Han, Runsheng; Li, Wenyao; Cheng, Ruihong (Frontiers in Earth Science, 2022)
As a new method of geophysical exploration in the full spatial domain, tunnel gravity exploration possess novel features; for example, it is free from electromagnetic interference and less affected by terrain, while offering high detection accuracy and being capable of overcoming a wide array of geophysical anomalies. The method shows its unique advantages in the field of deep prospecting and exploration. Based on the method of detecting high-density inclined orebodies in the tunnel gravity space, research on the deep space positioning of vertical orebodies is ongoing, and the dynamics of gravity anomalies are being revealed. Through the method’s application in the detection of concealed ore in the deep part of the Huangshaping skarn-type deposit in southern Hunan, China, clear results have been obtained. Our results show that tunnel gravity exploration solves the problem of ore bodies located in the deep parts of a high-density vertical ore body when a single tunnel or multiple tunnels are detected. This study not only expands on the theory and method of tunnel gravity exploration but also provides an important basis for the layout of deep exploration projects.